2008
DOI: 10.1007/978-3-540-77349-8_22
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cytomegalovirus-Accelerated Vascular Disease: Induction of Paracrine Factors That Promote Angiogenesis and Wound Healing

Abstract: Human cytomegalovirus (HCMV) is associated with the acceleration of a number of vascular diseases such as atherosclerosis, restenosis, and transplant vascular sclerosis (TVS). All of these diseases are the result of either mechanical or immune-mediated injury followed by inflammation and subsequent smooth muscle cell (SMC) migration from the vessel media to the intima and proliferation that culminates in vessel narrowing. A number of epidemiological and animal studies have demonstrated that CMV significantly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
110
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 54 publications
4
110
1
Order By: Relevance
“…HCMVinfected fibroblasts and ECs release >1000 proteins (i.e. the HCMV secretome) compared with mock-infected cells or herpes simplex virus type 1-infected cells (120,121). This includes laminins and >41 cytokines, chemokines and chemokine receptors that affect angiogenesis and wound healing (chemokines IL-6, osteoprotegerin, growth-regulated oncogene, C-C motif chemokine ligand [CCL] 3, CCL5, CCL7, CCL20, CXCL5, and CXCL16; receptors TNF receptors I and II and ICAM1; growth factors TGF-b1, hepatocyte growth factor and granulocyte macrophage (122) and VCAM1, which, in the early phase of infection, enhance transendothelial cell migration of inflammatory cells including monocytes, promoting angiogenesis by secretion of VEGF (120,123).…”
Section: Proangiogenic and Proliferative Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…HCMVinfected fibroblasts and ECs release >1000 proteins (i.e. the HCMV secretome) compared with mock-infected cells or herpes simplex virus type 1-infected cells (120,121). This includes laminins and >41 cytokines, chemokines and chemokine receptors that affect angiogenesis and wound healing (chemokines IL-6, osteoprotegerin, growth-regulated oncogene, C-C motif chemokine ligand [CCL] 3, CCL5, CCL7, CCL20, CXCL5, and CXCL16; receptors TNF receptors I and II and ICAM1; growth factors TGF-b1, hepatocyte growth factor and granulocyte macrophage (122) and VCAM1, which, in the early phase of infection, enhance transendothelial cell migration of inflammatory cells including monocytes, promoting angiogenesis by secretion of VEGF (120,123).…”
Section: Proangiogenic and Proliferative Effectsmentioning
confidence: 99%
“…HCMV encodes CC and CXC chemokine homologs, which further stimulate cell proliferation, chemotaxis and angiogenesis (121,125,126). The effect on SMC proliferation and migration in human blood vessels is observed both in vitro and in vivo (127,128).…”
Section: Colony-stimulating Factor) Hcmv Infection Of Ecs Induces Exmentioning
confidence: 99%
“…It has been shown that HCMV infection of ECs increases inflammation at the endothelium, promoting monocyte recruitment and extravasation, and increasing vascular permeability (1,(20)(21)(22)(23)(24)(25). Further, proinflammatory signaling elicited by the infection of vascular ECs contributes to angiogenesis and vascular disease (8,26,27).…”
mentioning
confidence: 99%
“…In addition, it has been associated with glioblastoma and other cancers (2), cardiovascular disease (3), and immune sensescence (4). Cytomegalovirus is named for the morphological changes -enlarged cells with nuclear and cytoplasmic inclusions-observed in cytomegalic inclusion disease (5).…”
mentioning
confidence: 99%